Comparing Intramedullary Nails Versus Dynamic Hip Screws in the Treatment of Intertrochanteric Hip Fractures on Post-operative Rehabilitation Outcomes:A Systematic Review Protocol. (30th November 2022) - Papp, Steve; Backman, Chantal; Konikoff, Lauren; Tanuseputro, Peter; Harley, Anne; Shah, Soha; Berdusco, Randa; Domecq, Marie-Cécile; Poitras, Stéphane; French-Merkley, Veronique; Beaulé, Paul E.
Background: Intertrochanteric hip fractures are treated by fixation with either an intramedullary (IM) Nail or Dynamic Hip Screw (DHS). It is unknown whether one surgery type has better post-operative rehabilitative outcomes for the hip fracture population. This systematic review aims to compare post-operative rehabilitation outcomes of intertrochanteric hip fractures treated via IM Nails versus DHS.Methods: We will conduct a systematic review following the Cochrane Handbook and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) format. A search strategy will be developed, and the following databases will be searched: MEDLINE, EMBASE, Cochrane Library, and Web of Science. Two reviewers will perform a two-step screening process and data extraction of included studies. Any disagreement will be resolved with a discussion or a third reviewer. Risk of bias and the quality of the studies will also be assessed. A narrative synthesis will be used for the data analysis.Conclusion: This systematic review will provide evidence for orthopaedic surgeons and rehabilitation clinicians to further improve patient rehabilitation outcomes post-hip fracture surgery.